2022
DOI: 10.1097/aog.0000000000004709
|View full text |Cite
|
Sign up to set email alerts
|

Preexposure Prophylaxis Acceptability Among Pregnant Individuals and Implications for Human Immunodeficiency Virus Prevention

Abstract: The authors thank the study participants for taking the time to share their experiences with us so that we can better understand how to increase access to and uptake of PrEP during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…This is an indication of gaps in health education, particularly within health facilities, which is where the women were recruited for the study. Whilst this study shows slightly higher proportions of PPW aware and also having correct knowledge about PrEP, several studies in similar populations in different settings in Sub-Saharan Africa and the United States of America have reported relatively low awareness and knowledge about PrEP ( 12 , 26 32 ). In South Africa, in a study among pregnant women from Cape Town knowledge about PrEP was only 33% ( 12 ) and in a study among young pregnant women aged 18–24 years old in KwaZulu Natal, none of the women had ever heard about PrEP before the survey ( 32 ).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This is an indication of gaps in health education, particularly within health facilities, which is where the women were recruited for the study. Whilst this study shows slightly higher proportions of PPW aware and also having correct knowledge about PrEP, several studies in similar populations in different settings in Sub-Saharan Africa and the United States of America have reported relatively low awareness and knowledge about PrEP ( 12 , 26 32 ). In South Africa, in a study among pregnant women from Cape Town knowledge about PrEP was only 33% ( 12 ) and in a study among young pregnant women aged 18–24 years old in KwaZulu Natal, none of the women had ever heard about PrEP before the survey ( 32 ).…”
Section: Discussioncontrasting
confidence: 72%
“…In Zambia, knowledge about PrEP among pregnant and breastfeeding was only 36% ( 28 ). In the United States approximately two thirds of pregnant women had never heard of PrEP before participating in the study ( 26 ). Of note is that even if the women were aware about PrEP, a majority tended to have incorrect knowledge about PrEP as an option for HIV prevention and also tended to have concerns about potential effects to their babies during pregnancy or breast feeding ( 27 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant and postpartum women faced the challenge of distinguishing between normal pregnancy symptoms and oral PrEP-related side effects. They were concerned that the observed side effects might be a danger sign for oral PrEP-exposed infants, which greatly reduced the willingness to use oral PrEP [46,47].Therefore, to alleviate maternal concerns about the side effects and safety of oral PrEP, medical providers should prioritize initiating early and frequent discussions with pregnant and postpartum women at high risk of HIV exposure, thoroughly explaining its safety profile, potential side effects, and providing informational support to enhance their awareness [48]. Furthermore, this review identified stigma against oral PrEP as a barrier to maternal oral PrEP implementation.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 papers were included in the review [16][17][18][25][26][27][28][29][30][31][32][33]. Of these 12 papers, four were described as descriptive qualitative studies, one was a mixed method study with thematic analysis of qualitative results, and the remaining seven qualitative research articles did not explicitly report the research methods.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation